Evaluación del Potencial Antimicótico del Aceite Esencial de Zingiber Officinale frente a cepas de Candida albicans. Estudio in Vitro - Alberca Torres, Estenia (2024)
In this in vitro study, the antifungal properties of Zingiber Officinale essential oil against Candida albicans, a pathogen commonly associated with fungal infections in humans, were evaluated. The research design was applied, cross-sectional, and experimental. Zingiber Officinale was used as the study population, with 6 kg of rhizomes utilized for essential oil extraction using the Soxhlet technique. Antifungal activity assessment was conducted using the Kirby Bauer technique, with 15 repetitions on culture plates and inclusion of negative (DMS) and positive (nystatin) controls. Hypothesis testing employed inferential statistics with ANOVA and Tukey's post hoc test at a 95% confidence level. Results demonstrated significant sensitivity of Candida albicans to Zingiber Officinale oil at concentrations of 100% and 50%, comparable to the effect observed with nystatin as the positive control. Analysis of variance identified statistically significant differences among treatment groups, confirming the efficacy of Zingiber Officinale oil as an antifungal agent. These findings underscore the importance of researching and developing therapies based on natural compounds to address fungal infections, thus significantly contributing to the fight against resistant pathogens.